Fresher with flavour: young women smokers' constructions and experiences of menthol capsule cigarettes and regular cigarettes - E. Gilbert; A. Ewald (BMC, 2021)
Abstract Background Flavour capsule cigarettes are one of the fastest growing segments of the tobacco market, and there is evidence that Australian young people are increasingly using menthol flavoured capsule cigarettes. This qualitative research examines how young women construct and experience menthol flavour capsule cigarettes as part of their smoking practices, and explores the perceived differences between menthol capsule cigarettes and regular cigarettes. Semi-structured face-to-face in-depth interviews were conducted with 41 Australian young women smokers, using a constructivist grounded theory approach. Results Findings reveal that the perceived fresh and improved taste of menthol and the ability to customise the smoking process positively contributed to young women's experiences of smoking menthol capsule cigarettes. In particular, menthol capsule flavour cigarettes were constructed by the young women as "fresh", "light" and "minty", and "popping" the menthol capsule allowed the young women to personalise their smoking experience. Conclusion These results indicate that specific public health campaigns and legislation should be developed to counter the powerfully alluring effects and the innovative appeal of menthol capsule cigarettes.